The association between mosaicism type and cognitive and behavioral functioning among males with fragile X syndrome. Issue 3 (8th December 2021) - Meng, Lu; Kaufmann, Walter E.; Frye, Richard E.; Ong, Katherine; Kaminski, Jennifer W.; Velinov, Milen; Berry‐Kravis, Elizabeth
Abstract: Mosaicism in fragile X syndrome (FXS) refers to two different FMR1 allele variations: size mosaicism represents different numbers of CGG repeats between the two alleles, such that in addition to a full mutation allele there is an allele in the normal or premutation range of CGG repeats, while methylation mosaicism indicates whether a full‐mutation allele is fully or partially methylated. The present study explored the association between mosaicism type and cognitive and behavioral functioning in a large sample of males 3 years and older ( n  = 487) with FXS, participating in the Fragile X Online Registry with Accessible Research Database. Participants with methylation mosaicism were less severely cognitively affected as indicated by a less severe intellectual disability rating, higher intelligence quotient and adaptive behavior score, and lower social impairment score. In contrast, the presence of size mosaicism was not significantly associated with better cognitive and behavioral outcomes than full mutation. Our findings suggest that methylation mosaicism is associated with better cognitive functioning and adaptive behavior and less social impairment. Further research could assess to what extent these cognitive and behavioral differences depend on molecular diagnostic methods and the impact of mosaicism on prognosis of individuals with FXS.